The US President's Malaria Initiative, Plasmodium falciparum transmission and mortality: A modelling study - Winskill,P; Slater,H; Griffin,J; Ghani,A; Walker,P (PLoS Medicine, 2017)
BackgroundAlthough significant progress has been made in reducing malaria transmission globally inrecent years, a large number of people remain at risk and hence the gains made are fragile.Funding lags well behind amounts needed to protect all those at risk and ongoing contributionsfrom major donors, such as the President’s Malaria Initiative (PMI), are vital to maintainprogress and pursue further reductions in burden. We use a mathematical modellingapproach to estimate the impact of PMI investments to date in reducing malaria burden andto explore the potential negative impact on malaria burden should a proposed 44% reductionin PMI funding occur.Methods and findingsWe combined an established mathematical model of Plasmodium falciparum transmissiondynamics with epidemiological, intervention, and PMI-financing data to estimate the contributionPMI has made to malaria control via funding for long-lasting insecticide treated nets(LLINs), indoor residual spraying (IRS), and artemisinin combination therapies (ACTs). Weestimate that PMI has prevented 185 million (95% CrI: 138 million, 230 million) malariacases and saved 940,049 (95% CrI: 545,228, 1.4 million) lives since 2005. If funding is maintained,PMI-funded interventions are estimated to avert a further 162 million cases (95%CrI: 116 million, 194 million) cases, saving a further 692,589 (95% CrI: 392,694, 955,653)lives between 2017 and 2020. With an estimate of US$94 (95% CrI: US$51, US$166) perDisability Adjusted Life Year (DALY) averted, PMI-funded interventions are highly costeffective.We also demonstrate the further impact of this investment by reducing caseloadson health systems. If a 44% reduction in PMI funding were to occur, we predict that this lossof direct aid could result in an additional 67 million (95% CrI: 49 million, 82 million) cases and290,649 deaths (95% CrI: 167,208, 395,263) deaths between 2017 and 2020. We have notmodelled indirect impacts of PMI funding (such as health systems strengthening